Independent Evaluation of Two Prototype Immunochromatographic Tests for Dengue Fever Developed by InBios. Issue 5 (11th January 2021) - Chen, Hua-Wei; Maldonado, Tania D; Lee, Cheng-Rei; Williams, Maya; Defang, Gabriel N; Ellison, Damon W; Van De Wyngaerde, Marshall; Rooney, Calli M; Wu, Shuenn-Jue L
ABSTRACT: Introduction: Dengue fever, caused by any of the four dengue viruses (DENV1–4), is endemic in more than 100 countries around the world. Each year, up to 400 million people get infected with dengue virus. It is one of the most important arthropod-borne viral diseases. Dengue's global presence poses a medical threat to deploying military personnel and their dependents. An accurate diagnosis followed by attentive supportive care can improve outcomes in patients with severe dengue disease. Dengue diagnostic tests based on PCR and ELISA platforms have been developed and cleared by the U.S. FDA. However, these diagnostic assays are laborious and usually require highly trained personnel and specialized equipment, which presents a significant challenge when conducting operations in austere and resource-constrained areas. InBios International, Inc. (Seattle, WA) has developed two rapid and instrument-free immunochromatographic test prototype devices (multiplex and traditional formats) for dengue diagnosis. Materials and Methods: To determine the performance of the InBios immunochromatographic tests, 183 clinical samples were tested on both prototype devices. Both assays were performed without any instruments and the results were read in 20 minutes. Results: The traditional format had better overall performance (sensitivity: 97.4%; specificity: 90%) than the multiplex format (sensitivity: 86.9%; specificity: 63.3%). The traditional format was superior in serotype-specific detection with 100% overall sensitivity for DENV1, DENV3, and DENV4 and 93.3% sensitivity for DENV2 compared to the multiplex format (91.7%, 78.3%, 83.3%, and 96.3% for DENV1, 2, 3, and 4, respectively). The traditional format was easier to read than the multiplex format. The multiplex format was simpler and faster to set up than the traditional format. Conclusions: The InBios traditional format had a better overall performance and readability profile than the multiplex format, while the multiplex format was easier to set up. Both formats were highly sensitive and specific, were easy to perform, and did not require sophisticated equipment. They are ideal for use in resource-limited settings where dengue is endemic. Based on our overall assessment, the traditional format should be considered for further development and used in the upcoming multicenter clinical trial toward FDA clearance.